Checklist and identification key to Brazilian species of Triplocania Roesler (Psocodea: ‘Psocoptera’: Psocomorpha: Ptiloneuridae), with four new cave-dwelling species - Da Silva Neto, Alberto Moreira; Aldrete, Alfonso N. García; Rafael, José Albertino; Ferreira, Rodrigo Lopes (Zootaxa, 2021)
Four species of Triplocania are described and illustrated (T. brancoi n. sp., T. ferratilis n. sp., T. pains n. sp., and T. zairae n. sp.), all based on male specimens collected in caves of the Brazilian state of Minas Gerais. An identification key is presented to the Brazilian species of Triplocania, based on males, together with information on both sexes and distributions.